Thymus Degeneration and Regeneration - Duah, Maxwell; Li, Lingling; Shen, Jingyi; Lan, Qiu; Pan, Bin; Xu, Kailin (Frontiers in Immunology, 2021)
The immune system’s ability to resist the invasion of foreign pathogens and the tolerance to self-antigens are primarily centered on the efficient functions of the various subsets of T lymphocytes. As the primary organ of thymopoiesis, the thymus performs a crucial role in generating a self-tolerant but diverse repertoire of T cell receptors and peripheral T cell pool, with the capacity to recognize a wide variety of antigens and for the surveillance of malignancies. However, cells in the thymus are fragile and sensitive to changes in the external environment and acute insults such as infections, chemo- and radiation-therapy, resulting in thymic injury and degeneration. Though the thymus has the capacity to self-regenerate, it is often insufficient to reconstitute an intact thymic function. Thymic dysfunction leads to an increased risk of opportunistic infections, tumor relapse, autoimmunity, and adverse clinical outcome. Thus, exploiting the mechanism of thymic regeneration would provide new therapeutic options for these settings. This review summarizes the thymus’s development, factors causing thymic injury, and the strategies for improving thymus regeneration.